Aktivitas antioksidan ekstrak sulur buah naga putih (Hylocereus undatus) dengan metode DPPH dan Rancimat - Hasim, Hasim; Andrianto, Dimas; Lestari, Ella Deffi; Faridah, Didah Nur (Jurnal Gizi dan Pangan, 2017)
The objectives of this study were to analyze phytochemical components, to determine total phenol and flavonoid content, and to test the antioxidant activity of dragon fruit vine extract. The results of phytochemical analysis showed acetone and ethyl acetate extracts contain alkaloids, flavonoids and steroids, while methanol extracts contained alkaloids, flavonoids and triterpenoids. Total phenol and flavonoid content determination results showed the highest concentration in acetone extract of 460.01 GAE mg / 100 g sample and 229.27 RUE mg/100 g sample. Extract of dragon fruit vine has a potencial as antioxidant by inhibition of free radical of DPPH with best IC50 value on acetone extract 25.32 mg / L. The results of antioxidant testing in lipid system using rancimat method obtained the highest protection factor on methanol extract of 1.64.